Land Use Change in the Cross-Boundary Regions of a Metropolitan Area: A Case Study of Tongzhou-Wuqing-Langfang - Linlin Dai; Zixin Zhan; Yeshuo Shu; Xiao Rong (Land, 2022)
Since the 1980s, metropolitan areas have increased worldwide due to urbanization and regionalization. While the spatial integration of the labor and housing markets has benefitted the development of cities within metropolitan areas, they have also brought great challenges for land governance; this is particularly evident in cross-boundary regions due to the complex relations between the markets and the regulations and between governments at different levels. Extensive research has been conducted on the city-level analysis of socioeconomic integration, land use development, and urban governance within metropolitan areas; yet, it is insufficient for understanding the intricate interplay between the various forces in such regions. This study aims to reveal the dynamics of land use change from 1990–2020 and its driving forces in the recent decade in the Tongzhou-Wuqing-Langfang (TWL) region—a typical cross-boundary area between Beijing, Tianjin, and the Hebei Metropolitan Area—using Landsat imagery. We employed the land-use dynamic degree, kernel density analysis, principal component analysis, and multiple linear regression to explore the spatiotemporal patterns of land use change and its driving factors at the district/county level. The results show that the general land use changes from cultivated and forest land to urban and rural construction land across the region. The speed of the trend varies considerably over time between different areas as the land use policies and regulations of each local government change. The population growth and the tertiary and secondary industry growth are the main driving factors for the change in construction land across the whole TWL region, while the urbanization rate and fixed asset investment have different impacts across the cross-boundary region. The results suggest that expanding the integration of land use policies and regulations in the cross-boundary region is urgently required.